Romanticism and Time Literary Temporalities - Laniel-Musitelli, Sophie; Sabiron, Céline (Open Book Publishers, 2021)
"'Eternity is in love with the productions of time'. This original edited volume takes William Blake's aphorism as a basis to explore how British Romantic literature creates its own sense of time. It considers Romantic poetry as embedded in and reflecting on the march of time, regarding it not merely as a reaction to the course of events between the late-eighteenth and mid-nineteenth centuries, but also as a form of creative engagement with history in the making. The authors offer a comprehensive overview of the question of time from a literary perspective, applying a diverse range of critical approaches to Romantic authors from William Blake and Percy Shelley to John Clare and Samuel Rodgers. Close readings uncover fresh insights into these authors and their works, including Frankenstein, the most familiar of Romantic texts. Revising current thinking about periodisation, the authors explore how the Romantic poetics of time bears witness to the ruptures and dislocations at work within chronological time. They consider an array of topics, such as ecological time, futurity, operatic time, or the a-temporality of Venice. As well as surveying the Romantic canon's evolution over time, these essays approach it as a phenomenon unfolding across national borders. Romantic authors are compared with American or European counterparts including Beethoven, Irving, Nietzsche and Beckett. Romanticism and Time will be of great value to literary scholars and students working in Romantic Studies. It will be of further interest to philosophers and historians working on the connections between philosophy, history and literature during the nineteenth century."